Answer:
See steps below
Step-by-step explanation:
We need to work with each side of the equation at a time:
Left hand side:
Write all factors using the basic trig functions "sin" and "cos" exclusively:
[tex]tan^2(x)\,cos^2(x)=\frac{sin^2(x)}{cos^2(x)} cos^2(x)=sin^2(x)[/tex]
now, let's work on the right side, having in mind the following identities:
a) [tex]sec^2(x)-1=tan^2(x)=\frac{sin^2(x)}{cos^2(x)}[/tex]
b) [tex]1-sin^4(x) =(1-sin^2(x))\,(1+sin^2(x))[/tex]
c) [tex]1-sin^2(x)=cos^2(x)[/tex]
Then replacing we get:
[tex]\frac{(sec^2(x)-1)\,(1-sin^4(x))}{1+sin^2(x)} =\frac{sin^2(x)(1+sin^2(x))(1-sin^2(x))}{cos^2(x)(1+sin^2(x)))} =\frac{sin^2(x)(1+sin^2(x))\,cos^2(x)}{cos^2(x)(1+sin^2(x)))}=sin^2(x)[/tex]
Therefore, we have proved that the two expressions are equal.